Irreducibility and compositeness in q-deformed harmonic oscillator algebras - Galetti, D.; Lunardi, J. T.; Pimentel, B. M.; Ruzzi, M. (Kluwer Academic/plenum Publ, 2002)
A study of the reducibility of the Fock space representation of the q-deformed harmonic oscillator algebra for real and root of unity values of the deformation parameter is carried out by using the properties of the Gauss polynomials. When the deformation parameter is a root of unity, an interesting result comes out in the form of a reducibility scheme for the space representation which is based on the classification of the primitive or nonprimitive character of the deformation parameter. An application is carried out for a q-deformed harmonic oscillator Hamiltonian, to which the reducibility scheme is explicitly applied.
Keywords: q-deformed algebras; q-deformed harmonic oscillator; deformation at roots of unity